Measuring Quality Determinants of Financial Statements - Widya Andelina; Aprih Santoso (Journal of Business and Management Review, 2021)
The research aims to study the impact of the role of internal audit, the application of regional accounting systems, and human resource competencies on the quality of financial statements. A sample of 141 employees according to the purposive sampling method and by distributing questionnaires. It turned out that the questionnaire returned was only from 138 employees. Data analyzed through moderate regression analysis (MRA) from the SPSS program. The results of the study stated that the role of internal audit has a negative impact on the quality of financial statements, the application of regional accounting systems and human resource competencies have a positive impact on the quality of financial statements